The Economic Benefits Associated with Florida's Artificial Reefs - Chuck Adams; Bill Lindberg; John Stevely (EDIS, 2006)
Florida has the most permitted artificial reefs in the nation. FE-649, a 6-page fact sheet by Charles Adams, presents the results of several studies to determine the economic benefits of artificial reefs. The author presents findings by region, with sections on Pinellas County, Dade County, Northwest Florida, Martin County, and the USS Speigel Grove (off Key Largo, FL). Published by the UF Department of Food and Resource Economics, August 2006.